乳腺癌的分子靶向药物及进展 - 张照辉 (临床药物治疗杂志, 2014)
目的：通过文献复习探讨乳腺癌的分子靶向治疗现状和进展。方法：查询近几年国内外乳腺癌分子靶向药物治疗进展的关键性文献并进行分析。结果：在乳腺癌的治疗中有明显疗效的分子靶向药物有人表皮生长因子受体2（HER2）的抗靶点药物曲妥珠单抗、拉帕替尼、帕妥珠单抗和曲妥珠单抗一DMl；有表皮生长因子受体( EGFR)靶向治疗的药物吉非替尼和西妥昔单抗，其他的靶点药物有血管内皮生长因子(VEGF)的靶向治疗(贝伐珠单抗)等。结论：目前不少分子靶向药物进入乳腺癌的临床应用，明显降低了乳腺癌患者的疾病复发风险，延长了晚期乳腺癌患者的生存期，其中抗HER2的靶向药物曲妥珠单抗是乳腺癌治疗最成功的靶向药物。分子靶向治疗是乳腺癌术后辅助治疗和晚期乳腺癌解救治疗中新的重要治疗手段。 Objective:To explore the status and research progress of the molecular targeted drugs for treatment of breast cancer .Methods: To view and analyze the data of research advances of molecular targeted drugs in the treatment of breast cancer domesticaly and internationaly in recent years.Results:The drugs have obvious curative effect in the treatment of breast cancer molecular targeted drugs including anti human epidermal growth factor receptor 2(HER2)such as trastuzumab , lapatinib, pertuzumab and T- DM1; anti Epidermal growth factor receptor (EGFR), such as cetuximab;other drugs with targets on vascular endothelial growth factor (VEGF) such as bevacizumab, etc. Conclusion:Currently, many molecular targeted drugs in the clinical treatment of breast cancer, significantly reduce the risk of disease recurrence of patients with breast cancer, prolong the survival period of patients with advanced breast cancer, in which trastuzumab is the most successful targeted drugs in treatment of patients with breast cancer. Molecular target therapy is an important new treatments in treatment of patient with breast cancer. 中国科技核心期刊(ISTIC) 0 z1 52-56